2023
DOI: 10.3390/app13052991
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of General Spatial Anticipation Skills for Basketball Referees

Abstract: In recent years, research has shown a positive correlation between sport-specific cognitive abilities and the performance of referees in different sports. However, it is still uncertain how much of the expertise exhibited by referees results from acquired sport-specific skills versus pre-existing general abilities. This study aimed to determine if the relationship between sport-specific abilities and expertise previously observed also applies to general visual abilities. In cooperation with the German basketba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Another decision-making factor that is critical in officiating is the concept of anticipation [ 50 , 51 ]. The concept of anticipation allows for officials to employ their knowledge structures to become efficient in their visual search to anticipate where to locate critical details in an upcoming event [ 52 , 53 ]. Advanced anticipation and visual search skills have been established in the literature as a critical quality for football officials at the elite level [ 50 , 54 ].…”
Section: Physiology Of Neuro-ophthalmic Principles For 3d Virtual On-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another decision-making factor that is critical in officiating is the concept of anticipation [ 50 , 51 ]. The concept of anticipation allows for officials to employ their knowledge structures to become efficient in their visual search to anticipate where to locate critical details in an upcoming event [ 52 , 53 ]. Advanced anticipation and visual search skills have been established in the literature as a critical quality for football officials at the elite level [ 50 , 54 ].…”
Section: Physiology Of Neuro-ophthalmic Principles For 3d Virtual On-...mentioning
confidence: 99%
“…Bieman et al employed eye-tracking techniques between elite and sub-elite officials that showed differences in eye gaze directions to produce towards earlier anticipation ocular movements [ 50 ]. Schrödter et al also found superior anticipation in elite referees compared to non-elite referees in basketball [ 53 ]. The concept of anticipation in officiating is very closely linked to the neuro-ophthalmic principles discussed above.…”
Section: Physiology Of Neuro-ophthalmic Principles For 3d Virtual On-...mentioning
confidence: 99%
“…The reason for the difference in the performance of expert and non-expert sports officials may be related to the anticipation of sports officials. Expert sports officials can rely on spatial or time anticipation to make predictions about the environment and determine behavior (Schrödter et al, 2023). Therefore, it is pivotal to examine how sports officials direct their vision to obtain information from the game, and subsequently make decisions at the perceptual-cognitive level, for a comprehensive assessment of their performance.…”
Section: Introductionmentioning
confidence: 99%